Minimizing TTP's involvement in signature validation - ZHOU, Jianying (Institutional Knowledge at Singapore Management University, 2006)
A digital signature applied on a message could serve as irrefutable cryptographic evidence to prove its origin and integrity. However, evidence solely based on digital signatures may not enforce strong non-repudiation. Additional mechanisms are needed to make digital signatures as valid non-repudiation evidence in the settlement of possible disputes. Most of existing mechanisms for maintaining the validity of digital signatures rely on the supporting services from trusted third parties, e.g., time-stamping and certificate revocation. Obviously, this is less efficient for on-line transactions. In this paper, we propose two new schemes for validating digital signatures as non-repudiation evidence that minimize the trusted third party's involvement.